2022
DOI: 10.3389/fnut.2022.850417
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dietary Supplements on Sleep Quality and Daytime Function of Shift Workers: A Systematic Review and Meta-Analysis

Abstract: BackgroundDietary supplements (DSs) may be useful for managing shift work disorder. But the efficiency of outcomes in clinical trials using simulated shift work populations as subjects is controversial. This review explores the potential role of DSs for improving sleep quality, daily functioning, and mood among shift workers in the real world.MethodsA related literature search was conducted in PubMed, Web of Science, Embase, and Cochrane Library databases from their inception to July 2021. Information was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Both drug and supplement uses were associated with shorter sleep duration. These results confirm the effects of supplements and drugs on sleep documented in the literature [25,50]. However, it should be noted that the sleep medications used, despite their beneficial effects on sleep, may carry some side effects, such as a lower physical and mental quality of life (QOL) [51].…”
Section: Discussionsupporting
confidence: 84%
“…Both drug and supplement uses were associated with shorter sleep duration. These results confirm the effects of supplements and drugs on sleep documented in the literature [25,50]. However, it should be noted that the sleep medications used, despite their beneficial effects on sleep, may carry some side effects, such as a lower physical and mental quality of life (QOL) [51].…”
Section: Discussionsupporting
confidence: 84%
“…Dietary intervention is a known effective strategy for maintaining good health among shift workers. Recently, Wu et al compiled data from 12 studies and found that dietary supplements like Vitamin C and Probiotics are beneficial to daily functioning, emotional regulation and sleep quality of shift workers [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, research indicates that probiotic administration may enhance the treatment and perspectives for these conditions [ 99 ]. Dietary supplements appear to confer a favorable impact on enhancing sleep quality and daytime functioning [ 100 ] ( Figure 2 ).…”
Section: Nutraceuticals and Their Impact On Mood Disordersmentioning
confidence: 99%